Formal literacy practices through play: exposure to adult literacy practices increases child-led learning and interest. Issue 1 (2nd January 2021) - Colliver, Yeshe; Arguel, Amael; Parrila, Rauno
ABSTRACT: Early literacy is largely acquired through child-led learning, yet current ways to support and enhance it may present problems of coercion and adult control. The Following in our Footsteps II intervention sought to circumvent such problems by teaching parent and educator pairs of 46 preschoolers how to make everyday literacy and numeracy processes (attention control condition) visible to children. Mixed-design ANOVAs indicated that children's literacy- and numeracy-related play increased significantly after four weeks of demonstrations. Reading and writing performance improvements were significantly greater in the Literacy group than in the Numeracy group. The results indicate that preschoolers' exposure to parents' and educators' everyday code-related literacy practices can enhance preschoolers' literacy interest and learning. They highlight an innovative way to increase exposure to code-related literacy skills and circumnavigate possible problems of coercion and adult control. Implications for literacy learning in play-based settings are discussed.